Recognition of facial emotional expression in amnestic mild cognitive impairment - Varjassyová, Alexandra; Hořínek, Daniel; Andel, Ross; Amlerova, Jana; Laczó, Jan; Sheardová, Kateřina; Magerová, Hana; Holmerová, Iva; Vyhnálek, Martin; Bradáč, Ondřej; Geda, Yonas E; Hort, Jakub (Journal of Alzheimer's disease, 2013)
We examined whether recognition of facial emotional expression would be affected in amnestic mild cognitive impairment (aMCI). A total of 50 elderly persons met the initial inclusion criteria; 10 were subsequently excluded (Geriatric Depression Score > 5). 22 subjects were classified with aMCI based on published criteria (single domain aMCI [SD-aMCI], n = 10; multiple domain aMCI [MD-aMCI], n = 12); 18 subjects were cognitively normal. All underwent standard neurological and neuropsychological evaluations as well as tests of facial emotion recognition (FER) and famous faces identification (FFI). Among normal controls, FFI was negatively correlated with Mini-Mental Status Examination scores and positively correlated with executive function. Among patients with aMCI, FER was correlated with attention/speed of processing. No other correlations were significant. In a multinomial logistic regression model adjusted for age, gender, and education, a poorer score on FER, but not on FFI, was associated with greater odds of being classified as MD-aMCI (odds ratio [OR], 3.82; 95% confidence interval [CI], 1.05-13.91; p = 0.042). This association was not explained by memory or global cognitive score. There was no association between FER or FFI and SD-aMCI (OR, 1.13; 95% CI, 0.36-3.57; p = 0.836). Therefore, FER, but not FFI, may be impaired in MD-aMCI. This implies that in MD-aMCI, the tasks of FER and FFI may involve segregated neurocognitive networks.
Keywords: senioři; Cognitive Dysfunction; senioři nad 80 let; Male; Famous Persons; Middle Aged; mužské pohlaví; studie případů a kontrol; rozpoznávání (psychologie); Amnesia; Aged, 80 and over; ženské pohlaví; Humans; světelná stimulace; Recognition, Psychology; kognitivní dysfunkce; lidé středního věku; emoce; významné osobnosti; Facial Expression; Emotions; Photic Stimulation; amnézie; Female; Aged; výraz obličeje; lidé; Case-Control Studies